PENGARUH KONSERVATISE DAN INVESTMENT OPPORTUNITY SET TERHADAP KUALITAS LABA PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - KHARISMA P, DAMBA (Jurnal Akuntansi AKUNESA, 2015)
Abstract This research aims to examine and analyze the influence of conservatism and investment opportunity set to earning quality of manufacturing companies. Variables tested in this study are conservatism, investment opportunity set and earning quality.The samples at this study are manufacturing companies listed in Indonesian stock exchange during period of 2011-2013. Based on purposive sampling method, the sample obtained are 64 companies. The hypothesis in this study were tested using multiple regression analysis.The result showed that conservatism and investment opportunity set have partial effect on earning quality. Keywords: Conservatisme, Investment Opportunity Set, Earning Quality